The Effect of Learning Media and Coordination To Forehand Top Spin Accuration on Table Tennis - Diki Syafwan Subagja; Nurlan Kusmaedi; Komarudin Komarudin (STKIP Muhammadiyah Kuningan, 2019)
This study aims to discuss the interaction of learning media and the coordination of avoiding hand movements from the forehand top spin of table tennis. This study uses an experimental method with a 2x2 factorial design, the study was conducted at UPI Sumedang Table Tennis UKM with a sample of 12 people and a sample placement to groups conducted by Random Assigment technique. The results of the study based on the two-way analysis of ANNOVA show the influence of learning media on the accuracy of forehand top spinning table tennis. Related interactions between instructional media with coordinating level on the accuracy of forehand top spinning table tennis are related to autorobot and spongewheel learning media for precision forehand spin over table tennis in the discussion group it was high and there was no difference between the autorobot and spongewheel learning media towards the accuracy of the forehand top spin table tennis in the low coordi- nation group. In conclusion, autorobot learning media is better used in groups with high coordination compared to spongewheel learning media, whereas in groups with low coordination learning media is useful to improve the accuracy of forehand top spin table tennis.